Comprehensive study of the early Yakut Sergelyakh burial of the XV — beginning of the XVI centuries - Bravina R.I.; Dyakonov V.M.; Nikolaev E.N.; Petrov D.M.; Syrovatskiy V.V.; Bagashev A.N.; Poshekhonova O.E.; Slepchenko S.M.; Razhev D.I.; Alexeeva E.A.; Zubova A.V.; Kuzmin Ya.V. (VESTNIK ARHEOLOGII, ANTROPOLOGII I ETNOGRAFII, 2016)
The paper presents a comprehensive study of graves which relate to rare burial sites of the early stage of ethnic history of the Yakuts. The burial belongs to an equestrian warrior. It is confirmed by the findings of the horse harness and fragments of weapons, including a part of a Central Asian composite bow which is unique to the Yakuts, arrowheads and a blade of palma (Siberian pole weapon). The vertebral pathologies and morphological features of femurs also point at riding as a usual way of transportation. Multiple injuries of bones indicate to an aggressive lifestyle. The death of the man was caused by a penetrating injury of the head with a bladed weapon. Craniological characteristics of the man correspond to the South Siberian populations characterized by a combination of Caucasoid and Mongoloid features. In this case, the latter prevails. The ritual funerary complexes correspond to the Ust-Talkin culture, which alongside with cranial features of the man enable us to associate Sergelyakh burial with Turkic part of the Sakha people, which is epically correlated with the legendary Elley Bootur.